Ischemic Stroke and Systemic Embolism in Warfarin Users With Atrial Fibrillation or Heart Valve Replacement Exposed to Dicloxacillin or Flucloxacillin. Issue 3 (13th November 2019) - Hellfritzsch, Maja; Lund, Lars Christian; Ennis, Zandra; Stage, Tore; Damkier, Per; Bliddal, Mette; Jensen, Peter Bjødstrup; Henriksen, Daniel; Ernst, Martin Thomsen; Olesen, Morten; Broe, Anne; Kristensen, Kasper Bruun; et al.
Abstract : The antibiotics dicloxacillin and flucloxacillin induce cytochrome P450‐dependent metabolism of warfarin. We explored the influence of these drug–drug interactions on the clinical effectiveness of warfarin therapy due to atrial fibrillation or heart valve replacement. Using the population‐based Danish registers, we performed a propensity‐score matched cohort study including around 50, 000 episodes of dicloxacillin/flucloxacillin matched to phenoxymethylpenicillin and to no antibiotic, respectively. We estimated hazard ratios (HRs) with 95% confidence intervals (CIs) by comparing 21‐day (days 7–28) risks of ischemic stroke/systemic embolism (SE) following initiation of each exposure. When compared with phenoxymethylpenicillin, dicloxacillin/flucloxacillin was associated with an HR of ischemic stroke/SE of 2.09 (95% CI 1.51–2.90; strongest for dicloxacillin (HR 2.17; 95% CI 1.56–3.02)). Use of an untreated comparator strengthened the association (HR 2.84; 95% CI 1.97–4.09). Dicloxacillin should be used with caution in patients receiving warfarin. This may also apply to flucloxacillin; however, more data on the risks associated with flucloxacillin exposure during warfarin therapy are needed.